The impact of free trade agreements on Middle East and North Africa exports of intermediate and final goods - Adriana Cardozo; Inmaculada Martínez-Zarzoso; Paula L. Vogler (The World Economy, 2021)
This paper is the first to analyse the impact of free trade agreements (FTAs) and the harmonisation of rules of origin (RoO) on Middle East and North African (MENA) countries' exports differentiating between final and intermediate goods for a global sample of trade partners. Data on exports from four MENA countries (Egypt, Jordan, Morocco and Tunisia) to 61 destinations over the period 1995–2016 are used to estimate a structural gravity model applying a Poisson Pseudo Maximum Likelihood (PPML) estimator. Moreover, the paper estimates the effect of the progressive adoption of the Pan-European-Mediterranean RoO. Results show that FTAs have been overall successful in increasing MENA exports. This is particularly true for FTAs that eliminate protection on agricultural products. In contrast to the existing literature, we find that the agreements concluded with European countries raise MENA exports, whereas no significant impact is found for the application of the Pan-European RoO.
Keywords: 330; free trade agreement; gravity model; Middle East and North Africa; panel data; Poisson Pseudo Maximum Likelihood